2022
DOI: 10.3389/fimmu.2022.996026
|View full text |Cite
|
Sign up to set email alerts
|

Blocking LAIR1 signaling in immune cells inhibits tumor development

Abstract: The current immune checkpoint blockade therapy has been successful in treating some cancers but not others. New molecular targets and therapeutic approaches of cancer immunology need to be identified. Leukocyte associated immunoglobulin like receptor 1 (LAIR1) is an immune inhibitory receptor expressing on most immune cell types. However, it remains a question whether we can specifically and actively block LAIR1 signaling to activate immune responses for cancer treatment. Here we report the development of spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…In a retrospective study, LAIR1 expression was found to associate to poor prognosis in invasive breast carcinoma ( 177 ), but also to resistance to PD1/PD-L1 inhibition in patients ( 178 ). Of interest, LAIR1 blockade by antagonist antibodies inhibited tumor development in a humanized mouse model by affecting, among others, the recruitment of pro-tumorigenic pDCs ( 179 ). In addition to blocking antibody, LAIR1-inhibitory signaling can be blocked also by taking advantage of LAIR2, a natural agonist ( 180 ) as proposed by a work using a dimeric LAIR2 Fc fusion protein to target collagens in tumors and reverse immune suppression ( 181 ).…”
Section: Irs Expressed By Pdcs and Their Role In Physiology And Tumorsmentioning
confidence: 99%
See 3 more Smart Citations
“…In a retrospective study, LAIR1 expression was found to associate to poor prognosis in invasive breast carcinoma ( 177 ), but also to resistance to PD1/PD-L1 inhibition in patients ( 178 ). Of interest, LAIR1 blockade by antagonist antibodies inhibited tumor development in a humanized mouse model by affecting, among others, the recruitment of pro-tumorigenic pDCs ( 179 ). In addition to blocking antibody, LAIR1-inhibitory signaling can be blocked also by taking advantage of LAIR2, a natural agonist ( 180 ) as proposed by a work using a dimeric LAIR2 Fc fusion protein to target collagens in tumors and reverse immune suppression ( 181 ).…”
Section: Irs Expressed By Pdcs and Their Role In Physiology And Tumorsmentioning
confidence: 99%
“…In addition to blocking antibody, LAIR1-inhibitory signaling can be blocked also by taking advantage of LAIR2, a natural agonist ( 180 ) as proposed by a work using a dimeric LAIR2 Fc fusion protein to target collagens in tumors and reverse immune suppression ( 181 ). The potential of LAIR1 blockade in cancer immunotherapy is currently emerging ( 179 , 182 ). However, since LAIR1 is widely expressed also by tumor cells, where it may induce either proliferation or inhibition depending on the tumor type ( 173 ), its therapeutic exploitation needs to be carefully tailored to each specific cancer microenvironment.…”
Section: Irs Expressed By Pdcs and Their Role In Physiology And Tumorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous reports and our results in this study associate LAIR1 expression on M2-like TAM with clinical outcomes (17,18), suggesting LAIR1 is a vital molecule that influences the functionality of M2-like TAM. As a result, there has been a growing interest over the past 3 years among scientists in investigating the role of LAIR1 in cancer progression and its potential as a target for therapeutic drug development (18)(19)(20)(21)(22)(23). Nevertheless, our current knowledge regarding the roles of distinct myeloid cell subsets in tumor progression, as well as the impact of LAIR1 on M2-like TAM functions and response to therapeutic drugs, remains limited.…”
Section: Introductionmentioning
confidence: 99%